Deployable Structures Based on Buckling of Curved Beams Upon a Rotational Input (Adv. Funct. Mater. 35/2021). (26th August 2021) - Mhatre, Saurabh; Boatti, Elisa; Melancon, David; Zareei, Ahmad; Dupont, Maxime; Bechthold, Martin; Bertoldi, Katia
Abstract : Deployable Structures In article number 2101144, Martin Bechthold, Katia Bertoldi, and co‐workers present a system of curved beams that leverage material elasticity and out‐of‐plane buckling to deploy from flat to diverse 3D configurations with a simple rotational input. The platform provides opportunities for the generation of functional, deployable systems (such as this variable lamp shade) that are low weight, compact, inexpensive, and easy to manufacture, and can be easily designed at different scales.